Pengaruh Insentif, Lembur, dan Kinerja Karyawan terhadap Hasil Kerja Karyawan pada PT. Sumber Mitra Permata Indonesia - Soegihartono, Soegihartono (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the influence of incentives, overtime, and employee performance on work outcomes at PT Sumber Mitra Permata Indonesia. The research method employed is regression analysis to examine the relationship between independent variables and employee work results. The findings indicate that incentives have a significant impact on work outcomes, where effectively administered incentives can enhance employee motivation and productivity. Furthermore, overtime also affects work results, but its impact depends on how the overtime policy is implemented. Poorly managed overtime can lead to fatigue and reduced performance in the long term. Meanwhile, employee performance shows a negative correlation among its components, suggesting that improvement in one aspect of performance may lead to a decline in another. These results are consistent with previous studies that emphasize the importance of incentives and overtime management in improving labor productivity. Therefore, companies are advised to implement more effective incentive strategies, balance overtime policies, and manage employee workloads proportionally to maintain both productivity and employee well-being. As such, sustainable improvement in work outcomes can be achieved, positively contributing to the overall performance of the company.